The Correlation between Breakfast Habits and Nutritional Status in School-Age Children at Adiarsa Barat 1 Elementary School - Herdina, Lula; Riski Sefrina, Linda; Elvandari, Milliyantri (Universitas Nahdlatul Ulama Surabaya, 2025)
The health and development of school-aged children are greatly influenced by their breakfast habits, which provide essential energy and nutrients for daily activities. However, many children often skip breakfast, which can affect their nutritional status. This research is an observational study with a cross-sectional approach conducted at Adiarsa Barat Elementary School 1. The subjects were 66 sixth-grade students selected through purposive sampling. Breakfast habits data were collected using a questionnaire, while nutritional status was measured based on height and weight. The correlation between breakfast habits and nutritional status was analysed using the Spearman Rho test with SPSS version 25.0. About 60.6% of respondents had breakfast 1-3 times a week, while 39.4% had breakfast 4-7 times a week. Most respondents (69.7%) had a normal nutritional status, with 3.0% experiencing malnutrition and 12.1% being obese. The analysis results showed a significant correlation between breakfast habits and nutritional status (p value = 0.000) with a correlation coefficient of -0.568. There is a significant correlation between breakfast habits and nutritional status in schoolchildren, although the negative direction of the correlation suggests that other influencing factors may be present.